Physical, technical, and tactical differences between continental soccer teams participating in the 2018 FIFA World Cup - Kvas-Cabral, V. C.; Martins, H.; Oneda, G.; Enes, A.; Moraes, I. F.; Leonel, D. F. (Journal of Physical Education and Sport, 2022)
Approach: In elite soccer, the physical, technical, and tactical variables must be analyzed in a complex and detailed way, aiming to improve the understanding of the teams' performances. However, these variables can be influenced by the playstyle of teams from the different continents. Purpose: This study aimed to compare the physical, technical, and tactical differences between the soccer teams from different continents (America, Europe, and Africa/Asia/Oceania) who participated in the 2018 FIFA World Cup. Forty-eight matches played during the group stage of the 2018 FIFA World Cup were analyzed. The data obtained were coded and calculated by a tracking system (GPS). The national teams were grouped according to the qualifiers for the 2018 FIFA World Cup and analyzed into three main groups (Europe: UEFA + Russia; America: CONMEBOL + CONCACAF; Africa/Asia/Oceania: CAF + AFC). Thirty-seven variables were analyzed and divided into tactical, physical, and technical parameters. Results: The results showed that athletes from the European teams were taller, covered a greater total distance faster (between 20 and 25 km.h-1), and spent more time in the opposing field (final third and penalty area) when compared to athletes from other continents. In contrast, athletes from the American continent were older (average age) and their attacks originated more from the left side of the field. Finally, Africa/Asia/Oceania athletes recovered a greater number of balls, had fewer corners, and their attacks originated more from the right side of the field. Conclusions: In summary, European teams had a more intense (physical parameters) and offensive playstyle (tactical) when compared to teams from other continents participating in the 2018 FIFA World Cup.